Telomere Maintenance Mechanisms in Cancer: Clinical Implications - Reddel, Roger R (Curr Pharm Des, 2014)
The presence of immortal cell populations with an up-regulated telomere maintenance mechanism (TMM) is an almost univer-sal characteristic of cancers, whereas normal somatic cells are unable to prevent proliferation-associated telomere shortening and have a limited proliferative potential. TMMs and related aspects of telomere structure and function therefore appear to be ideal targets for the development of anticancer therapeutics. Such treatments would be targeted to a specific cancer-related molecular abnormality, and also be broad-spectrum in that they would be expected to be potentially applicable to most cancers. However, the telomere biology of normal and malignant human cells is a relatively young research field with large numbers of unanswered questions, so the optimal design of TMM-targeted therapeutic approaches remains unclear. This review outlines the opportunities and challenges presented by telomeres and TMMs for clinical management of cancer.